Dictionaries and translation of contemporary novels - Vaxelaire, Jean-Louis (MonTi Monografías de Traducción e Interpretación, 2015)
Lexical problems do arise in many contemporary novels because of their polyphonic nature, mixing standard words, slang and technical terms. We must then ask ourselves if dictionaries may be useful to assist translators. We will see that for theoretical and practical reasons, this assistance is limited; a really useful dictionary should change its conceptual assumptions, therefore becoming a cultural dictionary in electronic form.